Desafios de gestão de abrigos temporários : uma análise sociológica de inseguranças e riscos no cotidiano de famílias abrigadas - Marchezini, Victor (2010)
From the interaction between natural phenomena like rains and a social organization, it can be occurs a quantity of environmental damages, material and human losses which can configured depending of the intensity of these a disaster. Human losses have been demanding more public policies of civil protection, mainly these families who are displaced from their home. These families can be characterized for the loss of the home s territory that was destroyed or located in risk areas, and after the evacuation commanded by the State, they were removed from their homes. In many times, these displaced families don t have founds to provided a temporary habitation or no have received an invitation to live temporally in their parents and friends houses, and their only alternative are going to a temporary shelter organized by the State. Temporary shelters were organized from the adaptation of public schools, sports gymnasiums, where displaced families will try to make a territory to reproduce social practices associated with their privates routines on their homes. This attempt will depend the relations among families and the relations between them and shelters administrators. The objective of this study was describing and analyzing sociologically how, after these process of loss the territory of home, displaced families try to produce their privates routines in public spaces like temporary shelters organized in contexts of disasters related to rains. The methodological procedures were based: bibliographic research, documental research and field research with qualitative methods. From the contributions of Sociology of Disaster, disasters can be comprehended like processes that were defined by the symbolic production, which it constituted by the agents in competition for the monopoly of official vision. In these power relations, temporary shelters were left in invisibility, and they have constituted in human s exclusion agglomerate (HAESBAERT, 2004), an extreme desterritorialization which reveal multiples desterritorializations that displaced families live intensively on temporaries shelters, a space of social suffering.